2012
DOI: 10.1016/j.neurobiolaging.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association of the apolipoprotein E epsilon 4 allele with incidence of dementia, cognitive impairment, and decline

Abstract: We examined longitudinal associations between ApoE4 + status and several cognitive outcomes and tested effect modification by sex. Data on 644 Non-Hispanic White adults, from the Baltimore Longitudinal Study of Aging (BLSA) were used. Dementia onset, cognitive impairment and decline were assessed longitudinally. After 27.5 years median follow-up, 113 participants developed dementia. ApoE4 + predicted dementia significantly (HR=2.89; 95% CI: 1.93-4.33), with non-significant sex differences. Taking all time poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 60 publications
5
109
1
1
Order By: Relevance
“…Possessing the APOE4 allele is a well-established risk factor for susceptibility to nonfamilial Alzheimer's disease (26), and a lower age of onset and higher risk of Alzheimer's disease (72,311,421). There is a greater risk for Alzheimer's disease in women with APOE4 compared to men (60). HT interacts with genetic background, as women specifically without an APOE4 allele have improved mood and cognition with estradiol-based HT (617).…”
Section: Estrogens and Androgens And Alzheimer's Diseasementioning
confidence: 99%
“…Possessing the APOE4 allele is a well-established risk factor for susceptibility to nonfamilial Alzheimer's disease (26), and a lower age of onset and higher risk of Alzheimer's disease (72,311,421). There is a greater risk for Alzheimer's disease in women with APOE4 compared to men (60). HT interacts with genetic background, as women specifically without an APOE4 allele have improved mood and cognition with estradiol-based HT (617).…”
Section: Estrogens and Androgens And Alzheimer's Diseasementioning
confidence: 99%
“…Additionally, female apoE4 carriers exhibit a significantly greater risk than male apoE4 carriers of converting to MCI, and from MCI to dementia (Altmann et al, 2014). ApoE4 is also more strongly linked to cognitive dysfunction (Beydoun et al, 2012) and brain atrophy (Holland et al, 2013; Liu et al, 2010) in women. Healthy older female, but not male, apoE4 carriers have decreased default mode network activity that is correlated with cerebrospinal fluid levels of tau protein (Damoiseaux et al, 2012).…”
Section: Mechanisms Underlying Sex Differences In Obesity and Alzhmentioning
confidence: 99%
“…Beydoun et al found a main effect of APOE on conversion from healthy aging to AD (Beydoun et al, 2012). Though the effect was numerically greater in women than men, the formal interaction was not significant.…”
Section: 2 Apoe and Gender: Clinical Outcomes In Healthy Aging And MCImentioning
confidence: 99%